Perpetrator type moderates the relationship between severity of intimate partner violence and recidivism - Goldstein, Daniel A. (Criminal justice and behavior, 2016)
The present study investigated the predictive utility of violence severity ratings on recidivism based on behavior-based subtypes (family only [FO] violent and generally violent [GV]) of intimate partner violence (IPV) perpetrators. Participants consisted of 328 men between the ages of 17 to 72 sentenced to probation in Lake County, Illinois between 2006 and 2008. The relationship between ratings of violence severity for the arresting event, based on victims? and perpetrators? accounts to responding police officers, and domestic violence recidivism for a 3-year postprobation completion/termination period was examined. Utilizing victims? accounts, the Kaplan?Meier log rank test revealed a significant main effect for violence severity. In addition, perpetrator type moderated the relationship between violence severity and postprobation recidivism, such that a positive association was found for GV men but not for FO violent men. Results corroborate the predictive utility of assessing violence severity at the arresting event, particularly within GV men of IPV.